Consensus‐based European guidelines for treatment of atopic eczema (atopic dermatitis) in adults and children: part I - Andreas Wollenberg; S. Barbarot; Thomas Bieber; Stéphanie Christen‐Zaech; Mette Deleuran; A. Fink‐Wagner; Uwe Gieler; Giampiero Girolomoni; S. Lau; Antonella Muraro; Magdalena Czarnecka‐Operacz; T. Schäfer; et al. (2018)
This guideline was developed as a joint interdisciplinary European project, including physicians from all relevant disciplines as well as patients. It is a consensus-based guideline, taking available evidence from other guidelines, systematic reviews and published studies into account. This first part of the guideline covers methods, patient perspective, general measures and avoidance strategies, basic emollient treatment and bathing, dietary intervention, topical anti-inflammatory therapy, phototherapy and antipruritic therapy, whereas the second part covers antimicrobial therapy, systemic treatment, allergen-specific immunotherapy, complementary medicine, psychosomatic counselling and educational interventions. Management of AE must consider the individual clinical variability of the disease; highly standardized treatment rules are not recommended. Basic therapy is focused on treatment of disturbed barrier function by hydrating and lubricating topical treatment, besides further avoidance of specific and unspecific provocation factors. Topical anti-inflammatory treatment based on glucocorticosteroids and calcineurin inhibitors is used for flare management and for proactive therapy for long-term control. Topical corticosteroids remain the mainstay of therapy, whereas tacrolimus and pimecrolimus are preferred in sensitive skin areas and for long-term use. Topical phosphodiesterase inhibitors may be a treatment alternative when available. Adjuvant therapy includes UV irradiation, preferably with UVB 311 nm or UVA1. Pruritus is targeted with the majority of the recommended therapies, but some patients may need additional antipruritic therapy. Antimicrobial therapy, systemic anti-inflammatory treatment, immunotherapy, complementary medicine and educational intervention will be addressed in part II of the guideline.